RANCANGAN SISTEM INFORMASI PERPUSTAKAAN PADA MAN 1 POLEWALI MANDAR - Hud, Abdullah; R, Cita St Munthakhabah; Bustamin, Bustamin (Universitas Nusantara PGRI Kediri, 2023)
Abstract Library information system to facilitate service to library members. MAN 1 Polewali Mandar so far has a library service system that is still in manual form so that in the process of serving library members it is considered slow as well in the process of recording book references and making library reports. Therefore it is necessary to do research to design library information system applications. The purpose of this information system is to provide convenience to library staff in collecting data on books and library members as well as in the process of printing reports. The steps taken in this case are system requirements analysis, system design, and system testing. This implementation uses the FoxPro visual programming language. Based on the research results, several conclusions can be drawn, namely: This software can be used to handle the process of inputting data, changing data, deleting and searching library data. Keyword: Information System, Library, visual foxpro.